Environmental temperature affects the dynamics of ingestion in the nectivorous ant Camponotus mus - Falibene, Agustina (2014)
Environmental temperature influences physiology and behavior in animals in general and is particularly determinant in ectotherms. Not least because temperature defines metabolism and body temperature, muscle activity in insects also strongly depends on this factor. Here, we analyzed how environmental temperature influences the dynamics of ingestion due to its effect on the sucking pump muscles in the nectivorous ants Camponotus mus. Feeding behavior and sucking pump activity during sucrose solution ingestion were first recorded in a natural environment in an urban setting throughout the day and in different seasons. Then, controlled temperature experiments were performed in the laboratory. In both situations, feeding time decreased and pumping frequency increased with temperature. However, different pumping frequencies under a same temperature were also observed in different seasons. Besides, in the laboratory, the volume of solution ingested increased with temperature. Consequently, intake rate increased when temperature rose. This change was exclusively promoted by a variation in the pumping frequency while volume taken in per pump contraction was not affected by temperature. In summary, environmental temperature modified the dynamics of ingestion and feeding behavior by directly affecting pumping frequency.